From Legal Structure to Legal Culture: Rethinking the Prosecutor’s School Outreach Program in Singaraja City - Ni Luh Made Madhusodani; Yuliartini, Ni Putu Rai; Mangku, Dewa Gede Sudika (Journal of Judicial Review, 2025)
This research discusses the effectiveness of the School Admissions Attorney Program in increasing students' legal awareness in Singaraja City. The research objectives are (1) to analyze the extent to which this program is effective in increasing students' legal awareness and (2) to identify and analyze various factors that hinder its implementation. This research uses an empirical legal approach with a descriptive nature, carried out at the Buleleng District Prosecutor's Office. Data was collected through document study, observation and interviews, with Non-Probability Sampling techniques using Purposive Sampling. The research results show that (1) although the Buleleng District Prosecutor's Office has attempted to provide legal education to students, this program has not been fully effective in reducing the number of students who become perpetrators of criminal acts, as shown by the fluctuation in the number of cases from year to year in Singaraja City. (2) The main obstacles in implementing this program include the large number of schools that must be handled by the Buleleng District Prosecutor's Office, clashes with other prosecutor's programs, and budget limitations. Nevertheless, the JMS Team continues to strive to overcome these obstacles by adjusting school visit schedules and optimizing the distribution of tasks, so that program implementation continues in the Intelligence sector of the Buleleng District Prosecutor's Office.